2010
DOI: 10.1386/jaah.1.1.19/1
|View full text |Cite
|
Sign up to set email alerts
|

Choral singing and psychological wellbeing: Quantitative and qualitative findings from English choirs in a cross-national survey

Abstract: Over 600 choral singers drawn from English choirs completed the WHOQOL-BREF questionnaire to measure physical, psychological, social and environmental wellbeing, and a twelve-item 'wellbeing and choral singing scale'. They also provided accounts of the effects of choral singing on quality of life,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
184
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(212 citation statements)
references
References 15 publications
19
184
0
9
Order By: Relevance
“…As people with stroke and PD experiencing communication difficulties and mood problems tend to have reduced QOL [91], it is perhaps surprising that CST participants have higher self-rated QOL than a large international sample of other people with disabilities. This is consistent with large-scale studies involving healthy adult members of international choirs, who also reported higher scores on the WHOQOL-BREF than the norm [43].…”
Section: Qol In Group Singingsupporting
confidence: 89%
See 1 more Smart Citation
“…As people with stroke and PD experiencing communication difficulties and mood problems tend to have reduced QOL [91], it is perhaps surprising that CST participants have higher self-rated QOL than a large international sample of other people with disabilities. This is consistent with large-scale studies involving healthy adult members of international choirs, who also reported higher scores on the WHOQOL-BREF than the norm [43].…”
Section: Qol In Group Singingsupporting
confidence: 89%
“…Small-scale choral studies with PD have shown improvements in QOL [40], speech intelligibility [41], breath control, and prosody [42]. Large-scale studies of choir participation with healthy older adults indicate improved QOL [43,44], social engagement [45,46], mood [47], immune functioning [48], and overall health [49].…”
Section: Choral Singing Therapy As a New Approach To Enhance Living Wmentioning
confidence: 99%
“…Studies on music making have also highlighted its benefits for well-being. Group singing interventions have pointed to increases in general well-being (Clift et al, 2010), self-esteem, social bonding and meaning (Cohen et al, 2006; Davidson, 2011; Tarr, Launey, & Dunbar, 2014). With older adults, interventions focused on engaging with musical instruments have provided evidence towards anxiety reduction (Hars, Herrmann, Gold, Rizzoli, & Trombetti, 2014), a sense of accomplishment (Perkins & Williamon, 2014), purpose, control, autonomy, social well-being (Creech, Hallam, Varvarigou, McQueen, & Gaunt, 2013), and increased cognitive function (Seinfeld, Figueroa, Ortiz-Gil, & Sandrez-Vives, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that particular forms of arts participation bring into play a distinctive profile of generative mechanisms with respect to well-being and health. A good example of this principle is provided by the recent work of Clift et al (2007Clift et al ( , 2008a, exploring the potential benefits of active involvement in choral singing. Analysis of choristers' accounts of their experience of singing has served to identify at least six mechanisms at work in this activity: positive affect, focused attention, deep breathing, social support, cognitive stimulation and regular commitment.…”
Section: Box G: Healing Arts Invest To Save Research Projectmentioning
confidence: 99%
“…The Sidney De Haan Research Centre for Arts and Health, established in 2004, is committed to researching the contribution of music and other participative arts activities in promoting the well-being and health of individuals and communities (Bungay & Skingley, 2008;Camic, 2008;Clift et al, 2007Clift et al, , 2008aClift et al, , 2008b. • arts and health is, and should be, firmly recognised as being integral to health, healthcare provision and healthcare environments, including supporting staff; • arts and health initiatives are delivering real and measurable benefits across a wide range of priority areas for health, and can enable the Department and NHS to contribute to key wider Government initiatives; • there is a wealth of good practice and a substantial evidence base;…”
Section: Sidney De Haan Research Centre For Arts and Health Canterbumentioning
confidence: 99%